Implementasi Tri Hita Karana dalam Pengembangan Ekowisata Menuju Pariwisata Berkelanjutan di Bukit Cemeng Kabupaten Bangli - I Wayan Wiwin (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
This study aims to examine the implementation of the Hindu philosophy Tri Hita Karana (three sources of happiness) in the development of Bukit Cemeng Ecotourism in Bangli Regency so that it can be a reference in the development of sustainable tourist attractions based on local wisdom in Bali. This study uses a qualitative method where data is collected through observation-participation techniques, in-depth interviews, and qualitative-interpretive analysis. The results of this study indicate that the implementation of the Tri Hita Karana concept in the development of Bukit Cemeng Ecotourism towards sustainable tourism can be seen from three aspects, namely the Parhyangan which concerns the relationship between humans and God, the Pawongan concerning human relationships with others, and the Palemahan, namely the human relationship with nature or environment. The contribution of this article emphasizes the importance of implementing local wisdom values ??in ecotourism development so that it can be sustainable in the future.